PERBEDAAN IMPLEMENTASI PROGRAM TAá¸¤FÄªáº’ DI SEKOLAH DAN MADRASAH DI SURAKARTA - Zulfa, Nurul Waridatil (Profetika Jurnal Studi Islam, 2018)
Nowdays, Islamic school becomes the choice of people. Ta?f?? programs becomes the excellence program in Islamic Elementary School or Madrasah Ibtidaiyah. The people believe and they are sure to choose Islamic education which has ta?f?? program in its curriculum. The objective of this research is to describe the imlementation of ta?f?? program, achievement target of memorizing al-Qur?an, the method that used to memorize al-Qur?an, evaluation that has been done by the teachers to the their students, supporting factors, the obstacles and the solution the overcome and also the implication of ta?f?? program toward the result of studens? learning. The kind of this research is qualitative study. The subject of this research consist of the principal, directur of ta?f?? program, teachers, students and parents in the ta?f?? program. The object of this research is SDTQ Al-Abidin Surakarta and MITTQUM Surakarta. The data collection techniques are observation, interview and documentation. The validity is determined by triangulation. The data technique analysis has been done by descriptive qualitative. The result of this research shows that (1) the background and the goals of tahfiz program to create ??fi? and ??fi?ah generation that have good intellectual based on al-Qur?an and hadith. (2) The achievement target in SDTQ Al-Abidin Surakarta is 10 juz and in MITTQUM Surakarta is 6 juz. The method that applied in SDTQ Al-Abidin Surakarta is wahdah, gabungan, kaisa, sima?i, jama? and juz?i. The method that applied in MITTQUM Surakarta is wahdah, tallaqi, kitabah, sima?i and juz?i. (3) Evaluation that has done by the teachers is run well as routine and periodical. For the examination, SDTQ Al-Abidin Surakarta has applied one juz examination. It is called al-Qur?an sertification. Ta?f?? examination that has been done in MITTQUM Surakarta is one juz in one period or we call it juziyyah and 5 juz examination in one period and in the graduation ceremony. (4) The Supporting factors of memorizing al-Qur?an are self motivation, parents and the environment. The obstacles of memorizing al-Qur?an are the lack of self motivation, bustle activity of parent and time management. The way to overcome the obstacles are making joyful learning process of ta?f?? program, improving the communication between the school and parents and having good cooperation between the teachers and the students about the time. (5)The implication of ta?f?? program toward the result of student?s learning are the students have good ability to memorize al-Qur?an. Sudents who have good ability to memorize al-Qur?an, they also have good ability in academic. It means that the ability of memorizing al-Qur?an as good as academic achievement. Saat ini sekolah Islam menjadi pilihan masyarakat. Program ta?f?? menjadi program unggulan di Sekolah Dasar Islam atau Madrasah Ibtidaiyah. Masyarakat semakin yakin memilih pendidikan yang berbasis Islam dengan muatan kurikulum program ta?f??. Penelitian ini bertujuan untuk mendiskripsikan implementasi program ta?f?? yang meliputi dasar dan tujuan, target capaian hafalan, metode untuk menghafal, evaluasi pembelajaran dan evaluasi hafalan, faktor pendukung, kendala dan solusinya, serta implikasi program ta?f?? terhadap hasil belajar siswa. Jenis penelitian ini adalah penelitian kualitatif. Subjek penelitian ini terdiri dari Kepala Sekolah/Madrasah, penanggung jawab program ta?f??, guru pengampu ta?f??, siswa dan wali murid. Objek penelitian ini adalah SDTQ Al -Abidin dan MITTQUM Surakarta. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Keabsahan ditentukan dengan triangulasi. Teknik analisis data dilakukan secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa (1) dasar dan tujuan program ta?f?? adalah menjadikan generasi yang ??fi? dan ??fi?ah yang intelektual dengan berlandaskan al-Qur?an dan hadits. (2) target hafalan di sekolah adalah 10 juz, sedangkan di madrasah adalah 6 Juz. Metode yang digunakan di SDTQ Al-Abidin antara lain metode wahdah, gabungan, kaisa, sima?i, jama? dan juz?i. Metode di MITTQUM Surakarta meliputi metode wahdah, tallaqi, kitabah, sima?i dan juz?i. (3) Evaluasi yang dilakukan guru meliputi evaluasi rutin dan berkala. Untuk ujian hafalannya di SDTQ Al Abidin disebut dengan sertifikasi al-Qur?an. Ujian di MITTQUM meliputi ujian juziyyah, ujian lima juz sekali duduk, dan ketika acara wisuda. (4) Faktor pendukungnya meliputi motivasi diri sendiri, orang tua, guru dan lingkungan. Kendalanya adalah kurangnya motivasi dari dalam diri, kesibukan orang tua, dan manajemen waktu. Solusinya adalah pembelajaran ta?f?? yang menyenangkan melalui cerita motivasi, memperkuat komunikasi antara sekolah dengan orang tua dan manajemen waktu antara guru dan murid. (5) Implikasi bahwa anak-anak yang memiliki kemampuan bagus dalam menghafal al-Qur?an cenderung nilai akademiknya juga bagus. Dengan pengertian bahwa kemampuan menghafal al-Qur?an berbanding lurus dengan prestasi akademik.